“OUR CHILDREN ARE THE ROCK ON WHICH OUR FUTURE WILL BE BUILT, OUR GREATEST ASSET AS A NATION”: MAXIMEN, SPRICHWÖRTLICHES UND ZITATE IN DER RHETORIK NELSON MANDELAS - Gläser, Rosemarie (Proverbium - Yearbook, 2015)
The article intends to examine Nelson Mandela’s individual style and rhetoric in his autobiography Long Walk to Freedom (1994) and in the volume of his collected speeches, Nelson Mandela in His Own Words. From Freedom to the Future (2003). The personality of Nelson Mandela, the first non-white South African president, was moulded by the native tradition of his Xhosa tribe, by the complex English culture which he interiorized in his adult life, and by the profound knowledge of Afrikaans language, history and politics which he ac-quired during his 27 years in prison. The repercussions of this varied cultural background may be found in Mandela’s use of proverbs, proverbial sayings, slogans, self-coined maxims and aphorisms, allusions to English and American literature, to antiquity and the Bible. On the whole, Nelson Mandela distrusted the ‘rhetoric’ of the former representatives of the Apartheid system. Instead, in his own political speech-es in the light of ‘nation building’ he applied structural devices and figures of speech from ancient rhetoric. Moreover, a rich imagery and well-chosen phraseological units add to Nelson Mandela’s linguistic/stylistic portrait.